Upaya Tiongkok Untuk Menjaga Hubungan Bilateral Dengan Jerman Melalui Diplomasi Panda - Khairur Rizki; Tartila , Dina; Rizki, Kurnia Zulhandayani (Review of International Relations, 2024)
This research examines the borrowing of pandas by China as a diplomatic effort and the image of the country. Therefore, when pandas began to become a profitable commodity, China began lending pandas for conservation in various countries accompanied by several agreements, one of which was with Germany. The use of pandas as a diplomatic tool to Germany has been carried out by China from 1980 to 2017. During this time, the two countries have produced a crucial panda loan agreement. This study aims to question the extent to which pandas can maintain relations between China and Germany. To explain the implementation of China's panda diplomacy in Germany, the author uses the soft power proposed by Joseph Nye Jr. and the concept of bilateral relations. Based on the concept of soft power, the author uses three indicators, namely culture, political institutions, and foreign policy. This research is a descriptive study, where the results show that panda diplomacy is able to maintain bilateral relations between China and Germany.